OTOMATISASI SAKLAR KENDARAAN BERMOTOR RODA 2 BERBASIS SISTEM SENSOR PENDETEKSI SUARA NIRKABEL SEBAGAI PENGGANTI SAKLAR KONVENSIONAL - Alfi Tranggono Agus Salim; Fredy Susanto; Agil Ferdiano Wennas; Hageng Firdausi; Rudy Prasetya; Muhammad Aji Pangestu; Sebastian Yudith Prastiawan; PUTRI NOVIA (Polinema Press, Politeknik Negeri Malang, 2020)
This project aims to change the conventional ignition mechanism to beautomatic by utilizing the microcontroller-based technology. The driver startsthe engine using a smartphone microphone and bluetooth smartphone thentransmitted to the HC-06 bluetooth module that connected to the Arduino uno tomove the 5v relay module wirelessly The driver can start the engine by openingthe Arduino bluetooth voice controller application on the smartphone and thencommands the sound then sends a signal to the Arduino Uno to start the enginewithout using a conventional ignition key. Wireless communication between thesmartphone and the actuator on a motorized vehicle can function properly if usedwith a range of distances from 1 meter - 50 meters with the condition that thesensor has been applied to the vehicle